Capstone Handbook - Rofuth, Todd W.; Piepenbring, Julie (2022)
Capstone Handbook has been produced as a practical guide for students in the final year of their MSW program. It is intentionally designed to provide brief overviews of the lock-step approach to completing a capstone or thesis project and includes activities to help partialize the steps that will culminate in the completion of the capstone. It contains 30 chapters spanning two semesters with each chapter providing chapter objectives, an introduction, chapter content, a summary of the chapter, end of chapter exercises, references and ancillary material. An overview of all key concepts required in a typical capstone provides students with a practical resource to guide them through the process of creating capstone proposals and final products. Lastly, the eBook’s intent is to afford students with some structure for getting starting by providing a number of templates.
Keywords: dept.swk